Bitcoin en Colombia (2021)
The financial system, especially cryptocurrencies such as "bitcoin", went through different crises over time, which has generated a lot of intrigue and mistrust among residents. The new era contracted new alternatives to carry out online transactions, where the paper money that we use today will take a back seat in the future.